Effects of antibiotic treatment strategies on feedlot cattle resistome and microbiome - Weinroth, Margaret, author; Belk, Keith, advisor; Morley, Paul, committee member; Martin, Jennifer, committee member (Colorado State University. Libraries, 2016)
The objective of this study was to evaluate resistome and microbiome changes in feedlot cattle exposed to commonly used antimicrobials. Sixteen pens of cattle (N=16) were randomly assigned to one of four antimicrobial treatments (n=4) resulting in a complete 2x2 factorial arrangement. The first factor was to treat Ceftiofur crystalline free acid (CCFA) to either the entire pen of animals (high dosage) or to one animal in the pen (low dosage). The second factor was the subsequent feeding of chlortetracycline (CTC) in feed to the entire pen of cattle or not administering CTC to a pen of cattle. Rectal fecal samples were collected from individual cattle within each pen on days 0 and 26. Deoxynucleic acid was extracted from individual fecal samples and pooled by DNA mass, so each pen had one composite sample on day 0 and day 26. Deoxynucleic acid was sequenced on an Illumina HiSeq 2000. Sequencing data (as known as reads) were aligned to a comprehensive antimicrobial resistance gene database and assigned to taxonomic labels. Sixty-eight antimicrobial resistance genes and 431 species were identified across all samples. Resistance to tetracycline was identified as the primary resistance at class level (66.9%) with resistance to Macrolide-lincosamide-streptogramin B (MLS) making up the majority of the remainder (26.2%). Resistance to tetracycline and aminoglycoside in the feces decreased (P < 0.05) in relative abundance from day 0 to day 26 when the cattle were fed CTC regardless of CCFA exposure. Beta-lactactams were the only class of resistance affected by the CCFA treatment, with low exposure CCFA pens exhibiting a smaller (P < 0.05) resistome on day 26 than those steers in high exposure CCFA pens, regardless of CTC treatment. These results indicate that the exposure to tetracycline for cattle may not be directly associated to the resistance to tetracycline in their feces. Further research is needed to explore more about this. Additionally, the decrease in resistance to aminoglycoside with no cattle exposed to anyaminoglycosides during the study raises the possibility of co-selection of resistant genes. Overall, the relative abundance of microbiome did not differ (P > 0.05) between pens of cattle with CCFA or CTC treatments but differed (P < 0.05) between day 0 and day 26. Overall microbiome relative abundance did not differ (P > 0.05) due to CCFA or CTC treatments but differed (P < 0.05) between day 0 and day 26. Changes in the microbiome over time affected all 19 phyla identified when all treatments were pooled together. It has been well established in humans that antimicrobial treatment changes in the microbiome (Khoruts et al., 2010; Preidis and Versalovic, 2009). While these findings are not as robust livestock, there is ongoing investigation establishing these same results that may lead to further understanding of how the microbiome of livestock responds to antibiotics.
Keywords: ceftiofur crystalline free acid; feedlot; resistome; chlortetracycline; antibiotic resistance; microbiome